Surface charges and J H Poynting’s disquisitions on energy transfer in electrical circuits - Matar, Maricel (2017)
Fil: Matar, Maricel. Universidad Nacional de Rosario. Facultad de Ciencias Exactas. Ingeniería y topografía. Departamento de Física; Argentina